Herpes Virus - Toshboltayevna, Akhmedova Saodat; qizi, Aminova Mohinur Normurod; qizi, Mengliboyeva Nozima Ikrom; qizi, Mardonqulova Gulnora Karim (European Journal of Life Safety and Stability (2660-9630), 2022)
Herpes virus is one of the most common viruses today. This article provides information about the herpes virus. Its types, distribution, origin are discussed. In addition, measures to prevent and treat this virus were discussed in detail.